Why do cities get involved in climate governance? Insights from Canada and Italy - Scanu, Emiliano; Cloutier, Geneviève (Environnement urbain / Urban Environment)

(untitled) (Institut National de Recherche Scientifique Centre Urbanisation Culture et Société, 2015)
Cities the world over are tackling climate change, even when their national governments are largely inactive in this area. Which factors trigger their implication? Through which kinds of policies do cities become engaged in this issue? Based on previous studies and on urban and multilevel governance theoretical frameworks, this article suggests some answers. An original analytical grid is developed and used to compare two cases in Canada and Italy. The results confirm that the way in which municipalities respond to climate change largely depends on their local and multilevel contexts, as well as on the potential benefits of climate action.